Pengaruh Dana Pihak Ketiga (DPK), Inflasi dan Bi Rate Terhadap Jumlah Penyaluran Kredit di Bank Negara Indonesia (BNI) Periode 2013-2017 - I Wayan Aristiyoga; A. A. Ketut Jayawarsa; Kompiang Bagiada (Warmadewa Economic Development Journal (WEDJ), 2018)
The purpose of this research is to find out how the influence of third party funds (DPK), inflation, and BI Rate partially and simultaneously on the amount of credit distribution at Bank Negara Indonesia (BNI). The data analysis technique used is the classical assumption test, multiple linear regression analysis. The results of third party funds research, inflation and the BI rate have a significant effect on the amount of lending to Bank Negara Indonesia. On variable third party funds have a positive and significant influence on the amount of credit distribution at Bank Negara Indonesia. From the t test on the Inflation variable has a negative and not significant effect on the amount of lending at Bank Negara Indonesia. From the t test on the variable the BI Rate has a negative influence and is not significant to the amount of lending to Bank Negara Indonesia.